Molecular di- and tetra-nuclear zinc(II) phosphates with sterically hindered aryl phosphate mono esters ligands. (1st November 2019) - Santra, Biswajit; Kumar, Vierandra; Kalita, Pankaj; Gupta, Vivek; Mandal, Debdeep; Chandra, Amitava; Joshi, Mayank; Choudhury, Angshuman Roy; Jana, Anukul; Chandrasekhar, Vadapalli
Graphical abstract: Di- and tetranuclear Zn(II) phosphates were prepared in the reactions of zinc(II) acetate and bulky aryl phosphate ligands in the presence of suitable co-ligands such as 1, 10-phenanthroine or pyrazole. Use of a linear co-ligand, 4, 4′-bipyridine afforded a one-dimensional coordination polymer. Abstract: Neutral dinuclear Zn(II) phosphates [Zn2 (L )2 (phen)2 (H2 O)2 ], (L = L2 ; (1 )), anionic dinuclear Zn(II)-phosphates [Et3 NH] + [Zn2 (L1 )4 (pyz)2 ] − (2 ) and tetranuclear double-4-ring (D4R) Zn(II) phosphates [Zn4 (L )4 (DMF)4 ] (5 –7 ), (L = L1 ; (3 ), L3 ; (4 ), L4 ; (5 )), [Zn4 (L1 )4 (pyz)2 (DMF)2 ] (6 ) and [Zn4 (L4 )4 (phen)2 (DMF)2 ] (7 ) were synthesized by using the bulky aryl phosphate ligands (L = 2, 6-(diphenylmethyl)-4-alkyl-phenyl substituted phosphates, ArOP(O)(OH)2 (Ar = 2, 6-CHPh2 -4-R-C6 H2 ; R = Me (L1 ), Et (L2 ), i -Pr (L3 ), and t -Bu (L4 )). The preparation of the complexes 1 –7 was accomplished at room temperature by the use of additional co-ligands such as phenanthroline or pyrazole. Use of the linear co-ligand, 4, 4′-bipyridine, affords the one-dimensional coordination polymer [Zn4 (L3 )4 (bpy)(DMF)2 ] n, 8 which is built by the fusion of tetranuclear Zn(II) motifs. All the compounds were characterized by single crystal X-ray diffraction techniques.